Leadership – Charismatic or Inspiring? An Inquiry into Regressive and Developmental Forms of Leadership. Issue 7 (3rd October 2021) - Stokes, Jon
ABSTRACT: Styles of leadership can be differentiated in terms of their outcome (constructive or destructive), mechanism (collaborative or coercive) and their effects on the followers (developmental or regressive). Two leadership styles, charismatic and inspiring, are described and contrasted. The former is regressive, based on a projection of the followers' ideal-ego onto and fusion with the idealized leader. The effect of inspiring leadership is developmental, the leader provides an exemplar of the followers' ego-ideal to which they aspire in a more realistic manner. Charismatic leadership promotes an "as if" mentality, inspiring leadership promotes a "what if" mentality. Charismatic leadership creates a divided state of mind, inspiring leadership encourages a more integrated state of mind. Actual leaders use both styles of leadership to varying degrees.